2020
DOI: 10.2147/dddt.s253876
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Fatostatin in Combination with Tamoxifen Induces Synergistic Inhibition in ER-Positive Breast Cancer</p>

Abstract: Background: Tamoxifen is the cornerstone of adjuvant therapy for hormone receptorpositive breast cancer. Despite its efficacy, limited drug sensitivity and endocrine resistance remain the important clinical challenges. The main objective of this study was to investigate fatostatin, which was found to sensitize breast cancer to the antitumour effect of tamoxifen both in vitro and in vivo. Methods: Fatostatin-induced ER degradation was detected by immunoprecipitation assay. The antitumour effect of fatostatin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In pancreatic cancer, both fatostatin and PF429242 inhibit cell proliferation and the growth of xenograft tumor by reducing SREBP-1 and its downstream signaling cascades, such as FASN and SCD-1 ( 17 ). Additionally, the combination of fatostatin with tamoxifen has a synergistic effect on the inhibition of PI3K/Akt/mTOR signaling in ER-positive breast cancer ( 140 ). Together, fatostatin mainly regulates the activation of SREBP-1/2 to block different cancer progressions, while it also regulates the accumulations of PUFAs and the PI3K/Akt/mTOR pathway.…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…In pancreatic cancer, both fatostatin and PF429242 inhibit cell proliferation and the growth of xenograft tumor by reducing SREBP-1 and its downstream signaling cascades, such as FASN and SCD-1 ( 17 ). Additionally, the combination of fatostatin with tamoxifen has a synergistic effect on the inhibition of PI3K/Akt/mTOR signaling in ER-positive breast cancer ( 140 ). Together, fatostatin mainly regulates the activation of SREBP-1/2 to block different cancer progressions, while it also regulates the accumulations of PUFAs and the PI3K/Akt/mTOR pathway.…”
Section: Targeting the Srebp-1 Signaling Pathway For Cancer Therapymentioning
confidence: 99%
“…The xenograft volume decreased after treatment with fatostatin ( 153 ). Moreover, the combined treatment with tamoxifen resulted synergic in reducing both in vitro cell proliferation and in vivo tumor growth in breast cancer ( 154 ).…”
Section: Cholesterol Metabolic Reprogramming In Cancer: Pharmacological Targetingmentioning
confidence: 99%
“…Previous results showed that fatostatin could inhibit SREBPs, which are master transcriptional factors that regulate DNL ( 26 ). Previous findings also showed that fatostatin could reduce the weight of ob/ob mice and possesses high antitumor properties against various cancers ( 27 , 28 ). Using our reporter mouse model, we monitored the role of fatostatin in DNL induced by high glucose and fructose water.…”
Section: Resultsmentioning
confidence: 88%